2010
DOI: 10.1590/s0001-37652010000200013
|View full text |Cite
|
Sign up to set email alerts
|

Diel variation in abundance and size of the seabob shrimp Xiphopenaeus kroyeri (Crustacea, Penaeoidea) in the Ubatuba region, Southeastern Brazil

Abstract: The objective of the present study was to analyze diel variation in the abundance and size of the seabob shrimp Xiphopenaeus kroyeri in the Ubatuba region, state of São Paulo, during the year 2000. In each season of the year, collections were made in the day and at night on 9 transects at depths ranging from 2 to 40 m. The estimated shrimp amount was of 28,878 individuals. Although the catch rate was higher during the day (15,853 shrimp), this did not differ significantly from the catch at night (13,025). The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
18
0
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 37 publications
(25 citation statements)
references
References 15 publications
(15 reference statements)
4
18
0
3
Order By: Relevance
“…However, the studies cited above did not find a specific difference in capture rates related to the type of sediment in the sampling area. The results of this study showed that variation in environmental parameters such as the sediment grain size and the temperature can also produce differences in capture rates, thus substantiating the studies performed by Bishop et al (2008) and Simões et al (2010). In agreement with the two studies cited above, Boschi (1989) and Costa et al (2004) observed that sediment type and temperature have been confirmed to exercise great influence on the distribution of P. muelleri.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…However, the studies cited above did not find a specific difference in capture rates related to the type of sediment in the sampling area. The results of this study showed that variation in environmental parameters such as the sediment grain size and the temperature can also produce differences in capture rates, thus substantiating the studies performed by Bishop et al (2008) and Simões et al (2010). In agreement with the two studies cited above, Boschi (1989) and Costa et al (2004) observed that sediment type and temperature have been confirmed to exercise great influence on the distribution of P. muelleri.…”
Section: Discussionsupporting
confidence: 90%
“…In general, P. muelleri follows the pattern proposed by Dall et al (1990) for penaeids, i.e., most marine shrimp species remain burrowed during the day and emerge at night. Diurnal burrowing activity is common in the majority of penaeids (STONER, 1991;VANCE, 1992;BISHOP et al, 2008;SIMÕES et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This preference for fine sediment is common in most of the peneid species like Penaeus esculentus Haswell, 1879, Metapenaeus endeavouri (Schmitt, 1926 (Gribble et al, 2007), Sicyonia dorsalis Kingsley, 1878 (Castilho et al, 2008b) and A. longinaris (Costa et al, 2005b). Very fine sand enables the shrimp's strategy of burying themselves to protect against predators and thus to decrease their energetic expenditure (Ameeri & Cruz, 1998;Simões et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…The spatial and temporal distribution of shrimps, as well as the onset at sexual maturity, growth, longevity, and spawning are affected by temperature, salinity, food availability, sediment structure and intrinsic factors (Bauer 1992;Castilho et al, 2007aCastilho et al, , 2007bCastro et al, 2005;Costa et al, 2005aCosta et al, , 2005bCosta et al, , 2007Simões et al, 2010).…”
Section: Introductionmentioning
confidence: 99%